Review of the Experience with Oil Stabilization and Savings Funds in Selected Countries - Fasano-Filho, Ugo (International Monetary Fund, 2000)
The main purposes of this paper are to review the operational modalities and experience of oil funds currently in place in Norway, Chile (copper), the State of Alaska, Venezuela, Kuwait, and Oman, and to draw some preliminary conclusions on their contribution to enhance fiscal management. The outcome so far of their experience has been mixed, with differences among countries reflecting the variety of objectives attached to the funds, the challenges in adhering to established rules, the institutional set-up. and the soundness of the overall fiscal discipline in each country (or state)